Online control of the gain drift with temperature of SiPM arrays used for the readout of LaBr3:Ce crystals. (1st October 2022) - Bonesini, M.; Bertoni, R.; Prata, M.; Rossella, M.
Abstract: LaBr3 :Ce crystals have been introduced for radiation imaging in medical physics, with photomultiplier or single SiPM readout. An R & D was pursued with 1/2″ and 1″ LaBr3 :Ce crystals, from different producers, to realize compact large area detectors (up to some cm 2 area) with SiPM array readout, aiming at high light yields, good energy resolution, good detector linearity and fast time response for low-energy X-rays. A natural application was found inside the FAMU project at RIKEN-RAL muon facility, that aims at a precise measure of the proton Zemach radius to solve the so-called "proton radius puzzle", triggered by the recent measure of the proton charge radius at PSI. The goal is the detection of characteristic X-rays around 130 keV. Other applications may be foreseen in medical physics, such as PET, and gamma-ray astronomy. A limiting factor is the gain drift of SiPM arrays with temperature, that give a deterioration of the detector's FWHM energy resolution. To solve this problem, a custom NIM module, based on CAEN A7585 digital power supply, was developed. Test results of the correction of gain drift with temperature for SiPM arrays from Advansid, Sensl, Hamamatsu will be presented. At the 137 Cs peak, an energy resolution better than 3% was obtained for a typical LaBr3 :Ce crystal, using Hamamatsu S13461 arrays. This compares well with best available results obtained with a PMTs.